Significance of PbO deposition ratio in activated carbon-based lead-carbon composites for lead-carbon battery under high-rate partial-state-of-charge operation. (1st April 2020) - Lin, Zheqi; Lin, Nan; Lin, Haibo; Zhang, Wenli
Abstract: Lead-carbon composites are effective additives in lead-carbon negative electrode due to their beneficial influences on the performance of negative electrode of lead-carbon battery operated under high-rate partial-state-of-charge duty. In this paper, to further investigate the effects of the lead monoxide (PbO) deposition ratio of activated carbon (AC) based lead-carbon composite additives, we prepared lead-carbon composites (termed as PbO@AC) with different controllable PbO deposition ratios successfully through a facile coupled chemical-deposition/pyrolysis strategy. The hydrogen evolution reaction of AC and lead-carbon electrode is effectively inhibited through the deposition of PbO. PbO@AC-2 sample with a PbO deposition ratio of 9.9% exhibits the best electrochemical performances when used as the negative electrode additive. The evidently enhanced performances of lead-carbon electrodes, such as rate capability and cycling life under high-rate partial-state-of-charge operation, indicate the beneficial effects of deposited PbO. Particularly, PbO@AC-2 battery exhibits the longest cycling life of more than 10, 000 cycles which is 1.956 times that of lead-carbon battery with AC as the negative electrode additive. The improved performances of lead-carbon electrode enabled by PbO@AC-2 originate from both the inhibition of hydrogen evolution reaction and the enhanced electrochemical reversibility of the Pb/PbSO4 redox reaction. PbO@AC-2 exhibits the best trade-off between inhibiting hydrogen evolution and building extra electrochemical active area for the deposition of Pb.